Developing Character-Based Digital Magazine as A Learning Media For Accounting Cycle of Service Company on Accounting Students - Rohmatunnisa, Layly Dwi (Unversitas Negeri Malang, 2017)
This study aims to create character-based digital magazine learning media that is applied to the first semester students majoring in accounting, State University of Malang. The material presented is material in the accounting cycle of a service company. This research is Research and Development (R & D). The data obtained in this study are quantitative and qualitative. Another source of research data from two lecturers as a material expert and instructional learning media expert, 36 accounting students, and 35 accounting education students, Universitas Negeri Malang. Data analysis techniques used in this research is a descriptive analysis of the percentage. Based on the expert assessment of the medium of learning, expert teaching materials, and field testing is limited by the user, the quality of instructional media that have been developed categorized as valid and worthy of use to the learning process with an average score of 93.8% by expert instructional media, 94.1% by material experts, and 82% by the user.Â Keyword: Character-Based Media, Digital Magazine, Accounting Cycle.DOI:Â 10.17977/um013v1i12017p043